2023
DOI: 10.4149/gpb_2021006
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of Apelin/APJ system on lipopolysaccharide-related cardiac dysfunction

Abstract: At present, the pathogenesis of sepsis-induced myocardial dysfunction (SIMD) is not completely clear and effective treatment measures are lacking. Apelin is an endogenous ligand of the angiotensin like G protein coupled receptor APJ and a cardiovascular peptide with multiple functions. Our aim is to analyze the protective effect and mechanism of Apelin/APJ system on lipopolysaccharide (LPS)-induced myocardial dysfunction. One hour before LPS treatment, apelin-13 or an APJ antagonist [Ala]-apelin-13 (F13A) was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…In this context, infusion of apelin-13 offers unique and optimized hemodynamic support, alongside cardioprotective effects and the modulation of circulatory inflammation, ultimately extending survival [ 34 ]. Apelin primarily exerts its effects on the cardiovascular system, particularly when myocardial injury occurs, by promoting apelin secretion to inhibit cardiac cell apoptosis, enhance myocardial contraction, and reduce myocardial injury [ 12 ]. Previous study has shown that the exogenous administration of apelin elicits positive inotropic effects in both healthy myocardium and in hearts affected by heart failure [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this context, infusion of apelin-13 offers unique and optimized hemodynamic support, alongside cardioprotective effects and the modulation of circulatory inflammation, ultimately extending survival [ 34 ]. Apelin primarily exerts its effects on the cardiovascular system, particularly when myocardial injury occurs, by promoting apelin secretion to inhibit cardiac cell apoptosis, enhance myocardial contraction, and reduce myocardial injury [ 12 ]. Previous study has shown that the exogenous administration of apelin elicits positive inotropic effects in both healthy myocardium and in hearts affected by heart failure [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several clinical investigations have substantiated that serum apelin-13 levels are elevated in septic patients, signifying its diagnostic value in the context of sepsis [ 11 ]. Furthermore, as sepsis frequently coincides with cardiomyocyte injury, animal studies have indicated that exogenous administration of apelin may mitigate inflammation, apoptosis, and augment autophagy in lipopolysaccharide-induced cardiac dysfunction [ 12 , 13 ]. Moreover, apelin-13 demonstrates the capacity to alleviate inflammatory responses induced by lipopolysaccharide and attenuate acute lung injury [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…K 2 Cr 2 O 7 -induced toxicity in H9c2 cells is a common cell model of Cr (VI) exposure to evaluate the cardioprotective pro les of bioactive reagents [6]. Apelin-13 can regulate the cardiovascular system [7]. Hence, the potential of apelin-13 was tested for its myocardiaprotective effect against toxicity induced by the toxins K 2 Cr 2 O 7 in H9c2 cells.…”
Section: Discussionmentioning
confidence: 99%
“…A relationship exists between TLR4/NF-κB and autophagy. In myocardial injury caused by sepsis, TLR4/NF-κB increases the autophagy in myocardial cells, thereby damaging them [72]. When a specific inhibitor is used to inhibit TLR4 and NF-κB activity, myocardial injury markers, such as creatine kinase and lactate dehydrogenase, decline, and inflammatory cytokines, such as IL-6 and TNFα, are downregulated.…”
Section: Autophagymentioning
confidence: 99%